PENGUJIAN MECHANICAL RUNNING DAN UNJUK KERJA POMPA SENTRIFUGAL SEBAGAI VALIDASI PERANCANGAN - Agung Sudarsono; Rosyida Permatasari; Alizar; Hezron Elyakim Potto; Mulus Harliady Pamungkas; Nur Aziz Sulaiman (Scientific Journal of Mechanical Engineering Kinematika, 2025)
This study validates the centrifugal pump design used in the cooling system of a 28 MW power plant project in Papua Island. Validation was conducted through mechanical and performance tests. Performance test based on ISO 9906 standards. Tests included measurements of bearing temperature, vibration, noise, and performance parameters such as head, flow rate, and efficiency. Results revealed deviations of ±4% and 0.36% in head and flow rate, along with a 6% efficiency reduction, all within the ISO 9906 Grade 2 tolerance limits. The analysis confirmed the pump meets design specifications and is suitable for implementation in the power plant's cooling system. These findings highlight the critical role of performance testing in ensuring the reliability and operational suitability of pumps.